A class of fourth order nonlinear boundary value problem with singular perturbation. (May 2021) - Lian, Wen; Bai, Zhanbing
Abstract: A class of singularly perturbed fourth order nonlinear differential equation is considered in this article. The existence of solution to boundary value problem (BVP) without singularly perturbed is obtained via nonlinear analysis method and upper and lower solution theory firstly. In addition, based upon some differential inequality techniques, as well as appropriate upper–lower solutions, the existence, uniqueness and corresponding asymptotic estimation of the solution to singularly perturbed boundary value problem (SPBVP) is considered.